2016
DOI: 10.1002/ps.4309
|View full text |Cite
|
Sign up to set email alerts
|

An artificial diet containing plant pollen for the mealybug predator Cryptolaemus montrouzieri

Abstract: Our results suggest that the pollen-based artificial diet can be used as an alternative food in the rearing of C. montrouzieri, and indicate its potential to support the mass production and wider application of this predator in biological control programmes. © 2016 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…The nutritional composition of food is a key factor that influences the development and reproduction of insect species (Bonte et al, 2010). An assessment of predator insect survival and reproductive performance indicates whether an artificial diet has potential for use in the mass rearing of the insect (Xie et al, 2017). Previous studies showed that adult reproductive performance was unfavorably affected by restricted food supply during the larval stages (Xie et al, 2015a, b).…”
Section: Discussionmentioning
confidence: 99%
“…The nutritional composition of food is a key factor that influences the development and reproduction of insect species (Bonte et al, 2010). An assessment of predator insect survival and reproductive performance indicates whether an artificial diet has potential for use in the mass rearing of the insect (Xie et al, 2017). Previous studies showed that adult reproductive performance was unfavorably affected by restricted food supply during the larval stages (Xie et al, 2015a, b).…”
Section: Discussionmentioning
confidence: 99%
“…This predatory ladybird beetle is native to Australia and has been introduced to at least 64 countries or regions for classical or augmentative biological control purposes since 1891 [12]. The success of C. montrouzieri can be attributed to its e cient predation of mealybug pests and easy mass rearing [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Whereas mealybugs produce wax secretions to protect themselves from a range of natural enemies, these wax secretions act as an attractant and oviposition stimulant for C. montrouzieri [12], indicating ladybird-mealybug specialization. Under laboratory and mass rearing conditions, C. montrouzieri can also feed on other Sternorrhyncha species (e.g., white ies, aphids and other coccids), lepidopteran eggs and even arti cial diets [14][15][16][17]. Some of these alternative diets can support the complete life cycle of the ladybird (provided that an arti cial oviposition substrate is supplied) but will to some extent decrease tness of the predators.…”
Section: Introductionmentioning
confidence: 99%
“…Among coccinellids, beneficial predators in biocontrol programs [ 7 , 8 , 9 ], the different species are protected by an array of chemical, behavioural, and/or morphological defense mechanisms evolved against predation and parasitism [ 10 , 11 ]. Reflex bleeding is an example of a chemical defense in which coccinellid larvae and adults emit distasteful and toxic droplets of hemolymph [ 12 ].…”
Section: Introductionmentioning
confidence: 99%